2018
DOI: 10.5897/ajps2018.1698
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Growth, Yield and Quality of Potato (Solanum tuberosum L.) Varieties at Bule, Southern Ethiopia

Abstract: This experiment was aimed to evaluate the performance of potato varieties in respect to growth, yield and quality attributes. A field experiment was carried out in Bule, Southern Ethiopia during the summer of 2017 under rain fed condition. The experiment was a single factor and arranged with randomized complete block design with 3 replicates. Treatments included different potato varieties (Bule, Gudenie, Jalenie, Belete, Degemegni and Local variety "Key Dench"). The results showed statistically significant var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
6
7
0
Order By: Relevance
“…Local variety combined with small-sized seed tuber produced the lowest marketable tuber yield ( Table 4 ). In the present study improved potato varieties generally produced more marketable yield compared to the local variety, which was also reported by other scholars [ 14 , 23 , 26 ].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Local variety combined with small-sized seed tuber produced the lowest marketable tuber yield ( Table 4 ). In the present study improved potato varieties generally produced more marketable yield compared to the local variety, which was also reported by other scholars [ 14 , 23 , 26 ].…”
Section: Resultssupporting
confidence: 90%
“…The observed variation in terms of days to 50% flowering could be attributed to intrinsic or genetic variation of the varieties in completing their vegetative growth and variation in environmental adaptability among the varieties. Similar study confirmed early flowering of local variety compared to the improved varieties [ 18 , 26 ].…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The DM values of statements were 29.8, 30.9, and 29.1 g/100 g, respectively. Highly significant differences (P<0.05) were observed among the DM values that may be a result of inherent differences in the genetic makeup of the plant clones (Getie, Madebo, & Seid, 2018). Fifteen out of the 28 genotypes investigated had DM values above a mean value of 25.2 g/100 g. That implies most (53.57%) had excellent DM values and compared favorably with the local checks used as control.…”
Section: Resultsmentioning
confidence: 86%